Physical Quality of the First Egg of Japanese Quail (Coturnix japonica L.) after Given Liquid Herbal Concoction - Hasan Basri; Meilinda Pahriana Sulastri (Universitas Wiralodra, 2021)
This study aims to determine the first egg's physical quality in Coturnix japonica L. after being given a liquid. The study is an experimental study with a Completely Randomized Design. In this study, the test animals were 24 Coturnix japonica L. randomly selected from 42 quail with 12 days old and average body weight of ± 37.67 g. They have been selected are divided into four treatment groups, i.e., P0: a control group with untreated drinking water, P1: 3 ml/liter water, P2: 6 ml/liter water, P3: 9 ml/liter water. Each treatment group consisted of 6 replications. Variables analyzed included egg weight, eggshell weight, yolk weight, albumen weight, egg yolk index, and egg quality index. The results showed that the addition of herbal concoction with the treatment of 3 ml, 6 ml, and 9 ml per 1 liter of drinking water on the physical quality of the first egg of Coturnix japonica L. including egg weight, yolk weight, albumen weight, shell weight, egg quality index, and yolk index statistically showed results were not significantly different (P>0.05 ), but the addition of herbal concoction did not have a negative effect on the physical quality of the first eggs of Coturnix japonica L.